Spatiotemporal Analysis of Urban Growth and PM2.5 Concentrations in Sylhet, Bangladesh - Mizanur Rahman; Lei Meng; Adam J. Mathews; Steven Bertman (Atmosphere)
Environmental impacts of urbanization, such as increased air pollution, pose significant challenges for developing countries. This study examines land cover changes and their relationship with particulate matter 2.5 (PM2.5) concentrations in two upazilas of Bangladesh from 2001 to 2019 using GIS and remote sensing techniques. Results show significant urban expansion (i.e., increase in built-up area) in both upazilas, corresponding with increasing PM2.5 levels. Linear regression reveals correlations between land cover types and PM2.5 levels. Mixed forests and waterbodies tend to be negatively associated with PM2.5 concentrations; on the other hand, built-up and barren land show a positive correlation with PM2.5. The most significant increase in built-up land and PM2.5 was in Madhabpur, indicating urgent environmental and health issues. This study emphasizes the critical role of sustainable urban planning and environmental conservation in mitigating urbanization’s adverse effects on air quality, advocating for preserving natural landscapes to maintain ecological balance, protecting urban health, and providing policymakers with insights to develop strategies addressing urban expansion and air pollution.